Three-dimensional visualization of tourist facilities as an element to provide information to tourist firms - B. Sadibekova; A.Makhmudova; S.Abdukhamidov; A.Mukhamadiev (International Journal on Human-Computing Studies, 2021)
If we look at the features of modern tourism, virtual reality models such as spherical panoramas, 3D, etc. play an important role in providing information to the tourism industry. Such technologies allow tourism companies to attract potential customers and go on a virtual journey.